The impact of meaning in life and professional happiness on the turnover intention of health care workers: a cross-sectional study from China - Yuting Huang; Huilin Zhang; Zuming Qin; Ying Zou; Zhiling Feng; Jiao Cheng (BMC, 2023)
Abstract Introduction The turnover and shortage of health care workers (HCWs) have been a worldwide problem for healthcare organizations. The primary aim of this study was to identify the factors influencing the intention of Chinese HCWs to leave their job, especially meaning in life and professional happiness. Methods This observational cross-sectional study, conducted among 1125 full-time HCWs, assessed demographic variables, meaning in life, professional happiness, and turnover intention by a survey. The survey was distributed to HCWs in three tertiary hospitals. The data were analyzed by T-tests, ANOVA, Kruskal-Wallis tests and hierarchical linear regression model. Results There were statistically significant differences in turnover intention of HCWs by gender, age, role, educational level, years in practice, and number of monthly night shifts. HCWs' meaning in life and professional happiness were negatively associated with the turnover intention. Furthermore, after controlling for other factors, meaning in life explained 3.7% of the turnover intention and professional happiness explained 13.4%. Conclusion In our study, positive psychological factors were related to turnover intentions. Professional happiness was the strongest predictor. Thus, health human resource managers should foster positive psychology among HCWs to reduce their turnover.